Issues of information security in the implementation of media texts - Niyazgulova А.А.; Ashenova С.В. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
The article deals with the issue ofinformation literacy, which is important forthe younger generation in light of the existing media risks of the modern communication environment. In the context of the existence of a democratic society, the media need to pay attention to the risks that may arise when implementing the concept of information security in the media space of the country. The media should use their own professional tools to implement this concept, being the main non-subjective mediator between the government and society. Information security in a research context is still a relative concept. Governments and states are the most important actors involved in determining the degree of danger, challenges, and threats to information security, in creating a balance of power in the international arena, preserving the identity of nation-states, in upholding their values, that is, the subjects of most components of information security, including including the development of its own unique media system. Information policy is of particular importance due to the fact that it largely determines the course and result of successful modernization in other areas, especially in conditions where Kazakhstan has actively entered the global information space. Without theoretical understanding and proposal of conceptual solutions, it is impossible to build a competent information policy in the twenty-first century.